Patronase Politik: Respon Bisnis Terhadap Program Tanggung Jawab Sosial Perusahaan - Intan Ravanza Rindiana (Jurnal Mengkaji Indonesia, 2023)
Abstract: Corporate Social Responsibility (CSR) is the concept of social responsibility of companies that invest in an area to be able to overcome problems that occur in a region. However, in the concept of CSR itself, there are many debates, especially regarding the relationships built between local government actors, companies, and communities in the management of CSR programs. Purpose: The objectives of this research activity are: (1) To determine state involvement in CSR programs, and (2) To determine the determination of CSR programs through political patronage. Design/Methodology/Approach: This study uses a literature review method with a qualitative research approach. The qualitative research approach is a process of research and understanding based on methods that investigate social phenomena and problems. Findings: Within the framework of the corporate social responsibility pyramid, the higher dimensions of responsibility are built on top of the lower ones, reflecting different levels of priorities and expectations in CSR practices. Originality/Value: The results prove that several forms of state involvement are common in CSR programs: (1) Arrangements and Policies that can influence companies to pay attention to social and environmental issues in their operations; (2) Incentives and Subsidies; (3) Public-Private Partnerships; (4) Law Enforcement and Supervision, the Government can supervise and monitor the implementation of CSR programs to ensure compliance and feasibility of practices carried out by the company; and (5) Community Empowerment. Here are some ways in which political patronage can influence the determination of CSR programs: (1) Resource Allocation: Political patronage can affect a company's allocation of resources to a particular CSR program. (2) Program Priorities: Political patronage can also influence the priorities of CSR programs chosen by the company. (3) Personal Gain; and (4) Creating a Positive Image: Political patronage can be used by companies to gain a positive image or public legitimacy.